The Environmental Responsibility And Steel Waste Management: A Case Study In A Company In Santa Maria –RS - Rick, Erwin Francisco; Ibdaiwi, Thiago Kader Rajeh; Almeida, Damiana Machado de; Corrêa, Jonathan Saidelles; Lopes, Luis Felipe Dias (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The Social Responsibility and Waste Management have become important approaches in organizational and social, due to increased concern for the environment, especially as regards the impact of production processes in nature and reducing the use of natural resources. Thus, the relevance of the study is related to the benefits arising from the use of sustainable procedures, allowing the reduction of damage to nature and contribute to raising the image of the organizations front of your customers and society. This study sought to demonstrate how the metal is recycled waste in the production of horseshoes in a company located in the city of Santa Maria/RS. This was made possible by checking the steel recycling rates and the identification of ways to reuse waste from this material. The research was qualitative in nature and as a strategy case study. Finally, it was revealed the involvement and commitment of the company because it uses clean processes of processing without contaminating the air and water sources, while performing the management of the steel waste within the local and regional recycling chain.